Distribuição dos recursos do FNE para o setor turístico entre os estados nordestinos, no período de 1998/2004 - Santos, Walquiria Cybelle Fernandes dos (2011)
The work aims to analyze the criteria that supported the geographic distribution of credit with FNE funds for the private tourism sector in the period 1998-2004 the Northeast, which is the maturing of a significant part of investments in the region I PRODETUR . The working hypothesis is that the credit allocation for the tourism industry, with FNE funds among the Northeastern states during the period analyzed broke with the trend towards concentration of credit in the richer economies of the region. The investigation concluded that there is enough evidence to enhance the degree of confidence in that hypothesis. However, the allocation criteria do not only benefited the poorest economies, nor directed lending while building on the weight that the tourism sector held in state economies